Sex-related differences in opioid administration in the emergency department: a population-based study. Issue 6 (14th April 2021) - Lau, Torey; Hayward, Jake; Vatanpour, Shabnam; Innes, Grant
Abstract : Background: Sex differences in pain experience and expression may influence ED pain management. Our objective was to evaluate the effect of sex on ED opioid administration. Methods: We conducted a multicentre population-based observational cohort study using administrative data from Calgary's four EDs between 2017 and 2018. Eligible patients had a presenting complaint belonging to one of nine pain categories or an arrival pain score >3. We performed multivariable analyses to identify predictors of opioid administration and stratified analyses by age, pain severity and pain category. Results: We studied 119 510 patients (mean age 47.4 years; 55.4% female). Opioid administration rates were similar for men and women. After adjusting for age, hospital site, pain category, ED length of stay and pain severity, male sex was not a predictor of opioid treatment (adjusted OR (aOR)=0.93; 95% CI 0.85 to 1.02). However, men were more likely to receive opioids in the categories of trauma (aOR=1.58, 95% CI 1.40 to 1.78), flank pain (aOR=1.24, 95% CI 1.11 to 1.38), headache (aOR=1.18, 95% CI 1.03 to 1.34) and abdominal pain (aOR=1.11, 95% CI 1.08 to 1.18). Pain category appears to be a strong determinant of opioid administration, especially back pain (aOR=6.56, 95% CI 5.99 to 7.19) and flank pain (aOR=6.04, 95% CI 5.48 to 6.65). There was significant variability in opioid provision by ED site (aOR 0.76 to 1.24). Conclusions: This population-based study demonstrated high variability in opioid use across different settings. Overall, men and women had similar likelihood of receiving opioids; however men with trauma, flank pain, headache and abdominal pain were much more likely to receive opioids. ED physicians should self-examine their analgesic practices with respect to possible sex biases, and departments should introduce evidence-based, indication-specific analgesic protocols to reduce practice variability and optimise opioid analgesia.